A Comparison of The Effectiveness of Digital Marketing Strategies on Instagram and TikTok in Boosting Sales for MSMEs in Denpasar - Kurniawan Joko Purnomo; Ida Bagus Ardhi Putra; D.A Gladysia Sistadanta (Publikasi Indonesia, 2026)
Digital technology has transformed the way micro, small, and medium enterprises (MSMEs) promote products, interact with consumers, and increase sales. In Denpasar, MSMEs increasingly use Instagram and TikTok as marketing platforms because both offer broad reach, interactive features, and relatively low promotional costs. However, each platform has different characteristics and effectiveness in influencing consumer behavior. This study aims to compare the effectiveness of digital marketing strategies on Instagram and TikTok in boosting MSME sales in Denpasar. This research used a descriptive qualitative approach involving MSME actors who actively utilized Instagram and/or TikTok for at least six months. Data were collected through in-depth interviews, direct observation of social media accounts, and documentation of promotional content, engagement, and sales-related information. The data were analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing, with source and method triangulation to ensure validity. The findings show that TikTok is more effective in attracting new audiences, creating viral exposure, increasing brand awareness, and encouraging impulse buying through short videos, live streaming, and affiliate collaboration. Meanwhile, Instagram is stronger in building credibility, displaying product catalogues, maintaining customer relationships, and supporting planned purchases. Therefore, the most effective strategy for MSMEs in Denpasar is a hybrid cross-platform model that positions TikTok as a traffic generator and Instagram as a conversion and customer-retention platform.